Abnormal Cortical Thickness Is Associated With Deficits in Social Cognition in Patients With Myotonic Dystrophy Type 1 - Serra, Laura; Bianchi, Guendalina; Bruschini, Michela; Giulietti, Giovanni; Domenico, Carlotta Di; Bonarota, Sabrina; Petrucci, Antonio; Silvestri, Gabriella; Perna, Alessia; Meola, Giovanni; Caltagirone, Carlo; Bozzali, Marco (Frontiers in Neurology, 2020)
Aim: Myotonic dystrophy type-1 (DM1) is the most common muscular dystrophy in the adulthood. Social cognition was previously demonstrated being impaired in DM1 patients in association with consistent changes in functional brain connectivity. Aim of this study was to investigate, using MRI, the cortical thickness in DM1 and its potential association with patients’ genetic triplet expansion and social cognition deficits. Methods: Thirty patients with DM1 were recruited to undergo the Social Cognition Battery Test (Prior et al., 2003) and a magnetic resonance imaging (MRI) scan at 3T. Twenty-six healthy subjects (HS) were also enrolled in the study to serve as controls for MRI data. T1-weighted volumes were collected from each subject and processed using CAT-12, a toolbox of SPM-12, to assess cortical thickness. Statistical comparisons between DM1 patients and HS were performed using a t-test model. Correlations between cortical thickness measures and genetics and cognitive features were assessed in patients using SPSS. Results: DM1 patients showed low performances in several subtests of the Social Cognition Battery. DM1 patients compared to HS showed reduced thickness in the right premotor cortex, angular gyrus, precuneus, and inferior parietal lobule. We observed significant associations between patients’ genetic load and thickness. Finally, significant associations were found between cortical thickness measures and various social cognition battery subtests. Discussion: the present study confirms the presence of widespread social cognition deficits in DM1 patients. Moreover, it reveals damage in the of DM1 brains that correlate with patients’ genetic loads. This reinforce the idea of DM1 as a neurodevelopmental disorder whose brain abnormalities contribute to account for the social cognition deficits observed in patients.